KONTRIBUSI PEKERJA PEREMPUAN TERHADAP PENDAPATAN KELUARGA PETANI DI DESA KOPIWANGKER KECAMATAN LANGOWAN BARAT - Natalia Deisi Yulandri Tumoka; Olly Esry Harryani Laoh; Welson Marthen Wangke (AGRI-SOSIOEKONOMI, 2019)
The purpose of the study was to find out how much the contribution of female workers to the income of farmer families in Kopiwangker Village, West Langowan District. The study lasted for two months, starting from October to November 2016. The sampling method was carried out in a simple randomized manner with the number of respondents as many as 30 people. This study used primary data and secondary data. Primary data obtained through direct interviews with respondents based on a list of questions that have been prepared. Secondary data was obtained directly from the Head of Village Office of Kopiwangker Village, West Langowan Subdistrict, and internet through google books and google scholars to obtain journal articles and theses related to the topic of this research, namely the contribution of female workers to the income of farmer families. The data obtained were analyzed descriptively and presented in table form. To find out the contribution of female workers tothe income of the farmer family, a contribution formula is used. The research results showed that the average income contribution percentage of female workers in Kopiwangker Village income to thefamily was 35.47% with an average income of Rp 1,233,333.33. The time allocation to spent on productive activities is 43.95 hours / month.*eprm*